PENERAPAN METODE MODELLING UNTUK MENINGKATKAN KEMAMPUAN MENGGOSOK GIGI PADA ANAK DOWN SYNDROME KELAS I DI SLB YPAC MAKASSAR - Akbar, Akbar; Saleh, Wizerti Ariastuti; Faizal, Faizal (-, 2025)
ABSTRACT The problem of this research is that Down Syndrome children at SLB YPAC Makassar are not yet able to brush their teeth appropriately and correctly independently. The formulation of the research problem is "How does the ability to brush teeth in Down Syndrome children at SLB YPAC Makassar increase after implementing the modeling method?" The aim of this research was to determine: 1) The ability to brush teeth before implementing the modeling method in class I Down Syndrome children at SLB YPAC Makassar. 2) The ability to brush teeth after applying the modeling method to class I Down Syndrome children at SLB YPAC Makassar. 3) Increasing the ability to brush teeth in Down Syndrome children at SLB YPAC Makassar through the application of modeling methods. The results of this study show that the ability to brush teeth in children with Down Syndrome level I at SB YPAC Makassar before the application of the modeling method for brushing their teeth was in the less capable category and after the application of the modeling method increased and entered the very capable category.